2022
DOI: 10.1002/term.3287
|View full text |Cite
|
Sign up to set email alerts
|

3D printed bioceramic scaffolds: Adjusting pore dimension is beneficial for mandibular bone defects repair

Abstract: Bioceramic scaffolds for repairing mandibular bone defects have considerable effects, whereas pore architecture in porous scaffolds on osteogenesis in specific structures is still controversial. Herein 6 mol% magnesium‐substituted calcium silicate scaffolds were fabricated with similar porosity (∼58%) but different cylindrical pore dimensions (Ø 480, 600, and 720 μm) via digital light processing‐based three‐dimensional (3D) printing technique. The mechanical properties, bioactive ion release, and bio‐dissoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…An overwhelming number of studies employed extrusion-related techniques (80%), and the six other strategies shared the other 20%. Within this minority, inkjet-associated strategies were the most representative [ 37 , 38 , 39 ] (6% of total), while digital light processing [ 40 , 41 ] and manual deposit or injection [ 42 , 43 ] were both 4%. Electrospinning [ 44 ], laser-assisted bioprinting [ 45 ] and selective laser melting [ 46 ] shared equally the 6% remaining (2% each).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An overwhelming number of studies employed extrusion-related techniques (80%), and the six other strategies shared the other 20%. Within this minority, inkjet-associated strategies were the most representative [ 37 , 38 , 39 ] (6% of total), while digital light processing [ 40 , 41 ] and manual deposit or injection [ 42 , 43 ] were both 4%. Electrospinning [ 44 ], laser-assisted bioprinting [ 45 ] and selective laser melting [ 46 ] shared equally the 6% remaining (2% each).…”
Section: Resultsmentioning
confidence: 99%
“…For three studies, physical properties of the material assessed constituted the focus of the investigations: porosity [ 40 , 41 ] and surface texture [ 81 ] were highlighted to be determining parameters for bone repair response.…”
Section: Resultsmentioning
confidence: 99%
“…Shim et al reported that porosity affects osteogenesis, with matrices with 30% porosity showing better osteogenic capacity than groups with 50% and 70% porosity [ 115 ]. Regarding pore size, the literature suggests that the ideal size should be between 400 to 600 μm [ 63 , 103 , 111 ]. Finally, the pore configuration should also be considered in terms of the dynamic stability of the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Blank bioceramic powder cannot be directly used in repairing bone defects due to fast degradation and loss. Therefore, various porous three-dimensional tissue engineering scaffolds were prepared and proved to have sufficient mechanical support, nutrient exchange, and induction of tissue ingrown, suggesting bioceramics in treating large-size bone defects [ 58 ].…”
Section: Tissue Engineering Technologies In Bone Regeneration and Repairmentioning
confidence: 99%